ANALISIS KUALITAS LAYANAN BONGKAR MUAT DI PT TERMINAL PETIKEMAS SURABAYA DENGAN METODE SERVQUAL DAN QFD - Bastian, Endhy; Ratnasari, Vita; Achmadi, Fuad (Universitas Nahdlatul Ulama Surabaya, 2018)
PT Terminal Petikemas Surabaya (TPS) has become one of the port services company has been trusted by various Indonesian and international companies in the management of international and domestic containers as well as various other loading and unloading services. PT TPS in providing international container management services is required to adjust its service level in accordance with international standards. Based on the Key Performance Indicator (KPI), the performance of PT TPS compared to some international ports in terms of Trund-Around Time (TRT), Gross Mover Per Hour (GMPH), and Berth Move Per Hour (BMPH) are still far behind with ports in UAE, Asia Pacific and India. The low performance of PT TPS based on the three indicators shows that the quality of service PT TPS still needs to be repaired. In this research, perception analysis and customer expectation with Service Quality (SERVQUAL) method to measure service quality of PT TPS. The gap between perception and customer expectation from Service Quality (SERVQUAL) is improved by Quality Function Deployment (QFD) method. And based on the two analysis, the preparation of strategies that should be applied by PT TPS to improve the quality of service. The results obtained show that all dimensions have satisfaction level “satisfied” which means that customers value the services provided by PT TPS is enough to meet expectations but still not maximal. Furthermore, Cartesius diagram analysis showed that there are 5 indicators that need improvement either immediately. The QFD analysis is performed to determine the recommended improvements on 5 indicators. Indicators that require top priority are indicators related to the competence of officers, especially administrative officers. So the management recommendation is to make Standard Operating Procedure (SOP) for each activity in port for administration officer